Impact factor of medical journals indexed in ScIELO Peru, 2015 - Contreras Sotomayor, Shamir Johnny (2016)
A critical point for any author before submitting an article is to determine which journal should be published (1). To do assesses indicators magazine as prestige, impact factor (FI) (2) coherence of the subject of the article, if paid for publishing, frequency of publication, language, indexing (3), visibility, scope (1, 4), among others.